ANTECENDENT KINERJA KARYAWAN PADA COFFEE SHOP DI PROVINSI DKI JAKARTA - Pramudianto Pramudianto; Uli Wildan Nuryanto; Lydia Hutama (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Human resource management in effort for improve employee, performance influenced by many factors, including work attachment to the company, career level that supports employee benefits and also the ability of employees carries out in accordance with applicable operational standards. For this reason, this research conducted to comprehensively determine the effect to work engagement, career path, and training standards on coffee shops performance in DKI Jakarta Province. This research used a sample of 75 employees from 18 coffee shops in DKI Jakarta as respondents, used analysis of multiple linear regression methods. Total of hypotheses tested are four hypotheses. The results from partial hypotheses show that; (1) Work Engagement has a significant effect on employee performance of coffee shops in DKI Jakarta; (2) Career path has a significant effect on employee performance of coffee shops on DKI Jakarta; (3) Training standards have a significant effect on employee performance coffee shop on DKI Jakarta; (4) while the results of the research simultaneously show that the work engagement, career paths and standard training simultaneously effect on employee performance of coffee shop on DKI Jakarta, with total effect as 79,8% while the 20,2% are the variable outside the research model. The highest effect of the third independent variable designated by training standard on employee performance. Therefore, to increase employee performance, it is need to carry out various activities that focus on training standard to improve employee performance in achieving goals in accordance to the company’s vision and mission.